2016
DOI: 10.1007/s00216-016-9924-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 24 personal care products in fish muscle and liver tissues using QuEChERS extraction coupled with ultra pressure liquid chromatography-tandem mass spectrometry and gas chromatography-mass spectrometer analyses

Abstract: A sensitive and selective quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction combined with dispersive solid-phase extraction (d-SPE) cleanup method was developed to simultaneously extract a wide range of personal care products (16 biocides, 4 synthetic musks, and 4 benzotriazoles) in fish muscle and liver tissues. In order to get satisfactory recoveries, different extraction parameters were optimized, including extraction salts and d-SPE materials, extraction solvents and acetic acid content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Apart from the determination of pesticides in fruits and vegetables of different nature 88 , up to now, a large majority of the d-SPE based involving GC for final analyte determination have dealt with the analysis of toxic microcontaminants in a variety of fat-containing foodstuffs 89 . These included, among many others, the determination of pesticides of different polarity in milk 39 , polychlorinated biphenyl (PCBs) in meat products 90 , personal care product in fish muscle and liver tissues 91 , the multiresidual analysis of 52 pesticides, 22 PCBs and the 16 EPA polycyclic aromatic hydrocarbons (PAHs) in honey using SPME for analyte preconcentration 38 , or the analysis of compounds produced during food processing, like acrylamide 41 , among others 92 . Interestingly, the reagents used in these applications kept rather similar to those employed in the original QueChers methodology, although the experience has demonstrated that their respective volumes and amounts required a careful optimization to ensure quantitative analyte recovery 39 .…”
Section: Sorption-based Extraction Techniquesmentioning
confidence: 99%
“…Apart from the determination of pesticides in fruits and vegetables of different nature 88 , up to now, a large majority of the d-SPE based involving GC for final analyte determination have dealt with the analysis of toxic microcontaminants in a variety of fat-containing foodstuffs 89 . These included, among many others, the determination of pesticides of different polarity in milk 39 , polychlorinated biphenyl (PCBs) in meat products 90 , personal care product in fish muscle and liver tissues 91 , the multiresidual analysis of 52 pesticides, 22 PCBs and the 16 EPA polycyclic aromatic hydrocarbons (PAHs) in honey using SPME for analyte preconcentration 38 , or the analysis of compounds produced during food processing, like acrylamide 41 , among others 92 . Interestingly, the reagents used in these applications kept rather similar to those employed in the original QueChers methodology, although the experience has demonstrated that their respective volumes and amounts required a careful optimization to ensure quantitative analyte recovery 39 .…”
Section: Sorption-based Extraction Techniquesmentioning
confidence: 99%
“…This approach was originally developed for low-fat fruit and vegetable matrices (Anastassiades et al 2003); subsequently, it was successfully applied for a variety of matrices and analytes by both gas and liquid chromatography techniques (Vera et al 2013;González-Curbelo et al 2015;Rejczak and Tuzimski 2015). Lately, this method, with some modifications, has been used to identify CECs in solid matrices such as animal feed (Lopes et al 2012), seafood (Cunha et al 2012), animal tissues (Pouech et al 2012;Berge and Vulliet 2015;Yao et al 2016), sewage sludge (Peysson and Vulliet 2013;Cerqueira et al 2014), sediments (Berlioz-Barbier et al 2014;Carmona et al 2014;Czech et al 2016;Santos et al 2016;Dos Santos et al 2018), and manure (Guo et al 2016). Berlioz-Barbier et al utilized QuEChRS for the first time to document 15 CECs (PPCPs, pesticides, and hormones) in sediment samples.…”
Section: Introductionmentioning
confidence: 99%
“…TCS in water samples was extracted using solid-phase extraction (SPE), while TCS in sediment samples was extracted by ultrasonic extraction combined with SPE purification (Chen et al, 2012). TCS in worm tissue was extracted by QuEChERS (quick, easy, cheap, effective, rugged, and safe) extraction combined with dispersive solid-phase extraction (d-SPE) clean-up method (Yao et al, 2016). Detailed extraction methods are given in the supporting information .…”
Section: Tcs Analysismentioning
confidence: 99%
“…The quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction combined with dispersive solid-phase extraction (d-SPE) clean-up method reported by Yao et al (2016) was applied to extract TCS in the tubifex. Briefly, 0.5 grams of tubifex tissue sample was weighted into a 50-mL polypropylene centrifuge tube, spiked with internal standard (50 ng) into each tube and vortexed for 30 s. Then samples were stored at 4 ˚C for 30 min for equilibration.…”
Section: Extraction Of Tcs In Worm Tissuementioning
confidence: 99%
See 1 more Smart Citation